Evaluating the Effectiveness of Investigation and Prosecution to Improve the Integrity of Law Enforcement in Indonesia - Saktiawan, Pratolo; Dirgantara, Febrian; Darmawan, Didit; Isnaini, Saifuddin; Waluyo, Argho (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze and evaluate the effectiveness of investigations and prosecution as key elements in law enforcement in Indonesia. This process is an important foundation to ensure justice, transparency, and respect for human rights. A normative juridical approach is used to examine the regulations governing investigations and prosecution, such as the Criminal Procedure Code and Law Number 2 of 2002 on the Indonesian National Police. The results showed that the effectiveness of investigations and prosecution is influenced by the professionalism of investigators, the application of modern technology, and adherence to legal principles. Key challenges include limited technical facilities, external pressures and complex bureaucracy, which often hamper the performance of law enforcement officers. To increase public trust in the legal system, Polri needs to prioritize transparency, community involvement, and strengthening synergies with judicial institutions. Good synergy between legal apparatus, judicial institutions, and the community has proven to be able to create a legal system that is inclusive and responsive to community needs. Strategic recommendations include institutional reform, increasing the capacity of apparatus, and developing effective supervisory mechanisms. This research is expected to contribute to the development of a more equitable and accountable legal system.